The creation of an active learning context for a Chinese class - Liu, Weiming; Devitt, Ann (NOVA Science Publishers, 2016)
This paper presents how the implementation of coteaching promote s an active learning environment in a beginners’ Chinese classroom. R esea rch has examine d ways in which students are encouraged to take active participation in learning ( Stern 1997; Mabrouk 2007 ; Clarke 2008) . As Mabrouk (2007, p.2) states, active learning ‘ generally refers to those teaching techniques that actively engage students in the classroom ’ . According to he r, active learning allows students to work either independently or in small groups , in small and large classes, at all levels. As to be reviewed in 2.1, coteaching covers a range of learning contexts. However, existing research has not extensively focused on a learning context in which students learn Chinese by participating in student - led coteaching in turn. The current study attempts to address this gap by attesting the possibility for students to drive their own learning in this specific learning context . The authors aim to explore the impact of the implementation of coteachin g on students’ learning process in terms of the following research questions: 1) Can coteaching encourage students to take responsibility for their own learning and the learning of o thers? 2) Can coteaching help students to learn the subject knowledge?
Conflict and Communication: A Changing Asia in a Globalizing World Language and Cultural Perspectives
PUBLISHED
Keywords: EDUCATION